MENGOPTIMALKAN PERAN PERGURUAN TINGGI DALAM MENGURANGI PRILAKU KORUPSI - Yanto, Oksidelfa Yanto; Samiyono, Sugeng; Walangitan, Semuel; Rachmayanthy, Rachmayanthy (Direktorat Jenderal Peraturan Perundang-undang, Kementerian Hukum dan Hak Asasi Manusia, 2020)
Abstract This research is purposed to determine how corruption occurs and then what steps must be taken to eradicate corruption and also to determine the role of universities in reducing anti-corruption behavior. The research method used in writing this research is a normative legal research method by conducting studies through library research or document studies. The results showed that the ways in which corruption occurred were among others by embezzling the practice of making rules that benefited certain parties, marking up projects, reducing the volume of work both in quality and quantity. Subsequently also the way a person commits a crime of corruption can go through a process that was initially small-scale which continues until the person concerned holds a high position. The steps that must be taken in eradicating corruption are building the rule of law, creating tangible conditions in all regions, the existence of activists, creating anti-corruption education, building moral education as early as possible, providing intensive religious education. While the role of universities in reducing corrupt behavior is to make universities a driving force because higher education institutions have a very strategic position in instilling an anti-corruption mentality. Higher education has the power to fight for the values of honesty.